2018
DOI: 10.1111/jfbc.12636
|View full text |Cite
|
Sign up to set email alerts
|

Effect of supplementation with a combination ofl‐arginine,l‐glutamine, and hydroxy methyl butyrate on cachexia: A systematic review

Abstract: Weight loss in the form of cachexia is a comorbid condition which is associated with delayed recovery, especially in cancer and human immunodeficiency virus (HIV)‐infected patients. Arginine (Arg), Glutamine (Gln), and the Leucine metabolite, Hydroxy methyl butyrate (HMB) are substrates which have been investigated due to their potential role in ameliorating muscle mass. We conducted a systematic review to appraise available studies assessing the effect of Arg, Gln, and HMB supplementation on improving body we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…However, a combination of these three amino acids in the previous trials led to a significant improvement in RBC volume, HCT and hemoglobin levels [ 52 , 57 ]. In a systematic review study, which conducted by Asghari et al, the effectiveness of Gln supplementation in cancer patients was evaluated and shown that the daily use of (Arg/Gln/HMB) mixture could improve some hematological parameters [ 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, a combination of these three amino acids in the previous trials led to a significant improvement in RBC volume, HCT and hemoglobin levels [ 52 , 57 ]. In a systematic review study, which conducted by Asghari et al, the effectiveness of Gln supplementation in cancer patients was evaluated and shown that the daily use of (Arg/Gln/HMB) mixture could improve some hematological parameters [ 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…The combination of Gln/Arg/HMB may improve recovery through various mechanisms in patients undergoing heart surgery. This compound had beneficial effects on vascular endothelial function [ 31 ], intestinal injuries [ 32 ], pressure ulcers [ 20 , 33 ], immune function [ 34 ], and anastomosis healing [ 35 ]. Moreover, it may prevent muscle wasting [ 36 ].…”
Section: Discussionmentioning
confidence: 99%